Comparison of the efficacy and safety of a proposed biosimilar MSB11456 with tocilizumab reference product in subjects with moderate-to-severe rheumatoid arthritis: results of a randomised double-blind study - Peter Baker; Anna Zubrzycka-Sienkiewicz; Kamilla Klama; Martin Ullmann; Corinne Petit-Frere; Joëlle Monnet; Andras Illes (RMD Open)
Objective To evaluate the efficacy, immunogenicity and safety of the proposed biosimilar MSB11456 versus European Union (EU)-approved tocilizumab reference product in patients with rheumatoid arthritis (RA) in a multicentre, randomised, double-blind, multinational, parallel-group study (NCT04512001).Methods Adult patients with moderate-to-severe active RA and inadequate clinical response to ≥1 disease-modifying antirheumatic drug (synthetic or biologic) receiving methotrexate were randomised to receive 24 weekly subcutaneous 162 mg injections of either MSB11456 or EU-approved tocilizumab. Equivalence between treatments was considered if the 95% CI (European Medicines Agency)/90% CI (US Food and Drug Administration) for the difference in mean change from baseline to week 24 in Disease Activity Score-28 Joint Count with erythrocyte sedimentation rate (DAS28-ESR) between treatments was entirely within prespecified equivalence intervals (−0.6 to 0.6 and −0.6 to 0.5, respectively). At week 24, patients were rerandomised to continued treatment or MSB11456. Secondary efficacy endpoints to week 52, and safety and immunogenicity to week 55 were also evaluated.Results At week 24, the least squares mean difference in the change from baseline in DAS28-ESR between treatments was 0.01 (95% CI −0.19 to 0.22) in the 604 randomised patients. Similarity between treatments was shown for all other efficacy, safety and immunogenicity endpoints, including in patients who switched from EU-approved tocilizumab to MSB114466.Conclusions Therapeutic equivalence was demonstrated for efficacy endpoints, and safety and immunogenicity analyses support the similarity of the two treatments. The results of this study strengthen the evidence that the proposed biosimilar MSB11456 and EU-approved tocilizumab exert similar clinical effects.